A case of diffuse infiltrating gastrointestinal stromal tumor of sigmoid colon with perforation. (January 2014) - Yamashita, Daisuke; Usami, Yu; Toyosawa, Satoru; Hirota, Seiichi; Imai, Yukihiro
<x xml:space="preserve">Abstract</x> Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal neoplasms of the gastrointestinal tract, and typically present as discrete well‐circumscribed but non‐encapsulated tumor masses. In this report, we describe a case of colonic perforation caused by an unusual form of GIST. A 72‐year‐old Japanese woman presented to the emergency department with acute abdominal pain. Under the provisional diagnosis of sigmoid colon perforation, a laparoscopic sigmoidectomy was performed. Although the tumor mass was undetectable during the preoperative examination, a spindle cell lesion with a diffuse longitudinal growth pattern replacing the muscularis propria was revealed by microscopic examination. The spindle cell lesion was exposed at the perforation, suggesting a causal relationship between the lesion and the perforation. The spindle cell lesion was KIT‐positive and had a mutation in the C‐KIT gene at exon 11. We diagnosed it as diffuse infiltrating GIST. We consider that the lesion would be a cause of the colonic perforation, and emphasize the importance of accurate diagnosis of the lesion by histological, immunohistochemical and genetic examinations.